What Is the Burden of Heterosexually Acquired HIV Due to HSV-2? Global and Regional Model-Based Estimates of the Proportion and Number of HIV Infections Attributable to HSV-2 Infection. (1st September 2021) - Silhol, Romain; Coupland, Helen; Baggaley, Rebecca F.; Miller, Lori; Staadegaard, Lisa; Gottlieb, Sami L.; Stannah, James; Turner, Katherine M. E.; Vickerman, Peter; Hayes, Richard; Mayaud, Philippe; Looker, Katharine J.; et al.
Abstract : Background: Biological and epidemiological evidence suggest that herpes simplex virus type 2 (HSV-2) elevates HIV acquisition and transmission risks. We improved previous estimates of the contribution of HSV-2 to HIV infections by using a dynamic transmission model. Setting: World Health Organization regions. Methods: We developed a mathematical model of HSV-2/HIV transmission among 15- to 49-year-old heterosexual, non–drug-injecting populations, calibrated using region-specific demographic and HSV-2/HIV epidemiological data. We derived global and regional estimates of the contribution of HSV-2 to HIV infection over 10 years [the transmission population-attributable fraction (tPAF)] under 3 additive scenarios, assuming: (1) HSV-2 increases only HIV acquisition risk (conservative); (2) HSV-2 also increases HIV transmission risk (liberal); and (3) HIV or antiretroviral therapy (ART) also modifies HSV-2 transmission risk, and HSV-2 decreases ART effect on HIV transmission risk (fully liberal). Results: Under the conservative scenario, the predicted tPAF was 37.3% (95% uncertainty interval: 33.4%–43.2%), and an estimated 5.6 (4.5–7.0) million incident heterosexual HIV infections were due to HSV-2 globally over 2009–2018. The contribution of HSV-2 to HIV infections was largest for the African region [tPAF = 42.6% (38.0%–51.2%)] and lowest for the European region [tPAF = 11.2% (7.9%–13.8%)]. The tPAF was higher among female sex workers, their clients, and older populations, reflecting their higher HSV-2 prevalence. The tPAF was approximately 50% and 1.3- to 2.4-fold higher for the liberal or fully liberal scenario than the conservative scenario across regions. Conclusion: HSV-2 may have contributed to at least 37% of incident HIV infections in the past decade worldwide, and even more in Africa, and may continue to do so despite increased ART access unless future improved HSV-2 control measures, such as vaccines, become available. Abstract : Supplemental Digital Content is Available in the Text.